Praecordial ST segment elevation. New technique for continuous recording and analysis. Issue 5 (May 1977) - Luxton, M R; Russell, D C; Murray, A; Williamson, D; Neilson, J M; Oliver, M F
Abstract : The measurement of praecordial ST segment elevation after myocardial infarction is of value in assessing the natural history of ischaemic injury and the effectiveness of intervention. Hand analysis is, however, time consuming and inaccurate. A technique for continuous recording from 35 praecordial leads and subsequent computer analysis is presented, together with illustrative case studies. Changes in body posture and in heart rate are of importance in subsequent data interpretation.